The Effect of Knowledge Sharing and Absorptive Capacity on Service Innovation Performance: A Study of Micro, Small and Medium Enterprises in Tarakan City: (Studies on Micro, small and medium enterprises (MSMEs) in Tarakan City) - Hidayat, Nurul (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
This research was conducted on micro, small and medium enterprises (MSMEs) in Tarakan City. To improve service innovation, micro, small and medium enterprises (MSMEs) in Tarakan City need knowledge sharing and absorption activities. This research was conducted on 150 workers in small, micro, and medium enterprises (MSMEs) in Tarakan City. Data collection was carried out using a survey method with a questionnaire. Survey responses submitted by respondents in this study indicate that knowledge sharing and absorptive capacity activities positively affect service innovation performance in micro, small and medium enterprises (MSMEs) in Tarakan City.